Making the health system work for the delivery of nutrition interventions. Issue 1 (20th July 2020) - King, Shannon E.; Sawadogo‐Lewis, Talata; Black, Robert E.; Roberton, Timothy
Abstract: Addressing malnutrition requires strategies that are comprehensive and multi‐sectoral. Within a multi‐sectoral approach, the health system is essential to deliver 10 nutrition‐specific interventions, which, if scaled up, could substantially reduce under‐5 deaths in high‐burden countries through improving maternal and child undernutrition. This study identifies the health system components required for the effective delivery of these interventions, highlighting opportunities and challenges for nutrition programmes and policies. We reviewed implementation guidance for each nutrition‐specific intervention, mapping the delivery process for each intervention and determining the health system components required for their delivery. We integrated the components into a single health systems framework for nutrition, illustrating the pathways by which health system components influence household‐level determinants of nutrition and individual‐level health outcomes. Nutrition‐specific interventions are typically delivered in one of four ways: (i) when nutrition interventions are intentionally sought out, (ii) when care is sought for other, unrelated interventions, (iii) at a health facility after active community case finding and referral, and (iv) in the community after active community case finding. A health system enables these processes by providing health services and facilitating care seeking for services, which together require a skilled and motivated health workforce, an effective supply chain, demand for services and access to services. The nutrition community should consider the processes by which nutrition‐specific interventions are delivered and the health system components required for their success. Programmes should encourage the delivery of nutrition interventions at every client–provider interaction and should actively generate demand for services—in general, and for nutrition services specifically.